Las emociones y su relación con el logro de aprendizaje de los niños/as de 5 años de la I.E.I N°303 Santa Rosa de Enace - Sierralta Tineo, Pablo Ciro (2011)
The treatments of residual waters, they involve to different types of microorganisms like bacteria, fungi, algae and water plants known like macrofits floating and fish as in this one I marry, they have demonstrated to be efficient in the water remediation with contents of organic material and toxic substances as Arsenic, Zinc, Copper, Chrome and Mercury. His importance takes root in his aptitude to be used principally in rural Communities and Houses, due to his low cost and the facility for his installation and operation of the systems of treatment. With the present work it is tried to contribute to the restoration of the river Cumbaza by means of the process of biorremediation consisting of the application of a system of infrastructure (Tank séptico, Reservoir of restoration and Tank by water to being re-used) and the inoculation of regional water plants as Lemna minor (lentejita of water), Pistia stratiotes known like (lechugilla, or Water hyacinth) and fish as the (tilapia) Oreochromis niloticus, presents in the water of the Tourist Playtime and of some piscigranjas of the zone. As well as also bacteria and own protozoans of the Tourist Playtime "The Mess ". The results of the present project, insitu and laboratory have been obtained by means of the application of the descriptive, analytical and comparative method, of agreement to the information taken of field by means of random samplings, with identification and recognition of factors pollutants, analysis of water and means contaminated that forms a part of the system of infrastructure of the Tourist Playtime in mention.